2022
DOI: 10.1111/trf.16958
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical DO2 with compensatory reserve during simulated hemorrhage in humans

Abstract: Background Based on previous experiments in nonhuman primates, we hypothesized that DO2crit in humans is 5–6 ml O2·kg−1 min−1. Study Design and Methods We measured the compensatory reserve (CRM) and calculated oxygen delivery (DO2) in 166 healthy, normotensive, nonsmoking subjects (97 males, 69 females) during progressive central hypovolemia induced by lower body negative pressure as a model of ongoing hemorrhage. Subjects were classified as having either high tolerance (HT; N = 111) or low tolerance (LT; N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Although LBNP ramp protocols have been used for investigation of the hemodynamic responses to progressive central hypovolemia [ 38 ], this is the first study in which the compensatory reserve has been analyzed with a constant ramp LBNP protocol that simulates both hemorrhage and resuscitation. Most previous LBNP protocols were designed to depressurize the vacuum chamber using a step profile in which negative pressure was maintained at a certain value [ 15 , 16 , 23 ] for a fixed period of time between depressurization steps. The ramped protocol applies a constant rate for both depressurization and repressurization, more accurately simulating both scenarios of whole blood hemorrhage or resuscitation, which are continuous processes in reality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although LBNP ramp protocols have been used for investigation of the hemodynamic responses to progressive central hypovolemia [ 38 ], this is the first study in which the compensatory reserve has been analyzed with a constant ramp LBNP protocol that simulates both hemorrhage and resuscitation. Most previous LBNP protocols were designed to depressurize the vacuum chamber using a step profile in which negative pressure was maintained at a certain value [ 15 , 16 , 23 ] for a fixed period of time between depressurization steps. The ramped protocol applies a constant rate for both depressurization and repressurization, more accurately simulating both scenarios of whole blood hemorrhage or resuscitation, which are continuous processes in reality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using this model they showed that a target CRM of 35% during whole blood resuscitation required only 40% of total blood volume lost to sustain adequate DO 2 to maintain hypotensive resuscitation [ 3 ]. Their most recent work establishes a CRM of 40% as a key threshold to ensure a patient at greatest risk for early onset of shock (i.e., individual with low tolerance to central hypovolemia) is at an adequate DO 2 level [ 23 ]. Unique to the current study is the varying rates of simulated whole blood hemorrhage and resuscitation used to develop the HRDN model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations